Sleep and hormonal changes in aging - Copinschi, Georges; Caufriez, Anne (Endocrinology and metabolism clinics of North America, 2013)
Age-related sleep and endocrinometabolic alterations frequently interact with each other. For many hormones, sleep curtailment in young healthy subjects results in alterations strikingly similar to those observed in healthy old subjects not submitted to sleep restriction. Thus, recurrent sleep restriction, which is currently experienced by a substantial and rapidly growing proportion of children and young adults, might contribute to accelerate the senescence of endocrine and metabolic function. The mechanisms of sleep-hormonal interactions, and therefore the endocrinometabolic consequences of age-related sleep alterations, which markedly differ from one hormone to another, are reviewed in this article.